KOMPETISI DAN PENGAMBILAN RISIKO DALAM INDUSTRI PERBANKAN NASIONAL - Aloysius Deno Hervino; Maria Margaretha Sumaryati (Jurnal Keuangan dan Perbankan, 2015)
This research aimed to prove that the degree of banking competition on collecting funds in Indonesia bankingindustry was able to explain the risk-taking lending behavior in its intermediary function, including theinfluence of some macro economy variables such as gross domestic product (GDP) and interbank money market(PUAB). Using error correction model engel granger (ECM-EG), the results of this research were both shortrunand long-run model. The degree of the banking competition had non-monotonic relationship on the risktakinglending behavior in Indonesia banking industry; moreover, the GDP had positif impact and the PUABhad a negtive impact on it.